A Description Of The Patient's Perception Of Leprosy In Kediri City Leprosy Hospital - Wahyu Tanoto; Nurul Laili (Chakra Brahmanda Lentera Institute, 2022)
Background: Leprosy is a disease caused by an infection of germs/bacteria that first attacks the peripheral nerve, then attack the skin, mouth mucosa, upper respiratory tract, reticuloendothelial system, eyes, muscle, bone, and testis, except central nervous. Perception is preceded by the process of sensing, which is the process of receiving the stimulus by the individual through the sensor device, or the process does not stop, but the stimulus is continued, and the following process is a preliminary process of the perception process. Methods: The purpose of this research is to know the description of patient perception of leprosy. Descriptive research design, as well as a large sample of 18 respondents who meet the criteria of research by using purposive sampling technique, instrument in the form of questionnaires, by using a single variable that is Patient Perception Perceptions About Leprosy Kediri. Data are measured and analyzed using percentage formulas and interpreted quantitatively. Results: In getting all the respondents, as many as 18 have a positive perception. Moreover, none of the respondents had a negative perception. This is caused by several factors influencing the patient's perception of leprosy: education and work. Conclusion: The discussion results found that education and occupational factors can affect the positive perception of patients about leprosy, and it is expected that leprosy patients diligently perform treatment and still perceive leprosy disease towards the positive.